NILAI EKONOMI TIDAK LANGSUNG EKOSISTEM MANGROVE DI DESA BUHIAS KECAMATAN WORI KABUPATEN MINAHASA UTARA - Meike Ismalsi Gogali; Jardie A. Andaki; Srie J. Sondakh; Siti Suhaeni; Victoria E.N. Andaki; Djuwita R.R. Aling (AKULTURASI: Jurnal Ilmiah Agrobisnis Perikanan, 2023)
Abstract The aims of this study were: to identify the indirect benefits of the mangrove ecosystem in Buhias Village, Wori District, North Minahasa Regency and to calculate the indirect economic value of the mangrove ecosystem in Buhias Village, Wori District, North Minahasa Regency. The benefits expected from the research include: increasing knowledge about the indirect economic value of mangrove forest ecosystems in Buhias Village, Wori District, North Minahasa Regency and fulfilling one of the requirements in completing education at the Faculty of Fisheries and Marine Sciences, Sam Ratulangi University, Manado. The method used in this research is case study. The data collected is in the form of primary data and secondary data. Primary data was obtained through interviews and direct observation in the field to see directly the condition of the mangrove forest and the condition of the community. Secondary data was obtained from existing data at the village office or from previous studies. The data analysis used is descriptive qualitative and quantitative analysis. The indirect economic value of the mangrove ecosystem in Buhias Village, Wori District, North Minahasa Regency, namely: IDR 137,478,804.40 / year or IDR 1,374,788,044.08 / 10 years, wave breakers amounting to IDR 425,082,852.73 / year or IDR 4,250,828 .527.33 / 10 years, for seawater intrusion protection it amounts to IDR 4,708,226.25 / year or IDR 47,082,262.50 / 10 years, and for abrasion prevention it amounts to IDR 42,286,050.00/ year or IDR 422,860,500.00/ 10 years. With a total of IDR 567,312,033.38 / year or IDR 5,673,120,333.80 / 10 years. Keywords: economic value; indirect benefits; mangroves; Buhias Village Abstrak Tujuan penelitian ini, yaitu: mengidentifikasi manfaat tidak langsung ekosistem mangrove di Desa Buhias Kecamatan Wori, Kabupaten Minahasa Utara dan menghitung nilai ekonomi tidak langsung ekosistem mangrove di Desa Buhias Kecamatan Wori, Kabupaten Minahasa Utara. Manfaat yang diharapkan dari penelitian antara lain: menambah pengetahuan tentang nilai ekonomi tidak langsung ekosistem hutan mangrove di Desa Buhias Kecamatan Wori, Kabupaten Minahasa Utara dan memenuhi salah satu syarat dalam menyelesaikan pendidikan di Fakultas Perikanan dan Ilmu Kelautan Universitas Sam Ratulangi Manado. Metode yang digunakan dalam penelitian ini yaitu studi kasus. Data yang dikumpulkan berupa data primer dan data sekunder. Data primer diperoleh melalui wawancara, dan observasi langsung ke lapangan untuk melihat langsung keadaan hutan mangrove dan keadaan masyarakat. Data sekunder diperoleh dari data yang sudah ada pada kantor kelurahan ataupun dari penelitian-penelitian terdahulu. Analisis data yang digunakan ialah analisis deskriptif kualitatif dan kuantitatif. Nilai ekonomi tidak langsung ekosistem mangrove di Desa Buhias Kecamatan Wori Kabupaten Minahasa Utara, yaitu: Rp.137.478.804,40/tahun atau Rp1.374.788.044,08/10 tahun, penahan gelombang berjumlah Rp425.082.852,73/tahun atau Rp4.250.828.527,33/10 tahun, untuk penahan intrusi air laut berjumlah Rp4.708.226,25/tahun atau Rp47.082.262,50/10 tahun, dan untuk pencegah abrasi berjumlah Rp42.286.050,00/tahun atau Rp422.860.500,00/10 tahun. Dengan total Rp567.312.033,38/tahun atau Rp5.673.120.333,80/10 tahun. Kata kunci: nilai ekonomi; manfaat tidak langsung; mangrove; Desa Buhias